Differential regulations of abscisic acid-induced desiccation tolerance and vegetative dormancy by group B3 Raf kinases in liverworts - Jahan, Akida; Yamazaki, Yuto; Islam, Mousona; Ghosh, Totan Kumar; Yoshimura, Nami; Kato, Hirotaka; Ishizaki, Kimitsune; Shinozawa, Akihisa; Sakata, Yoichi; Takezawa, Daisuke (Frontiers in Plant Science, 2022)
Phytohormone abscisic acid (ABA) plays a key role in stomata closure, osmostress acclimation, and vegetative and embryonic dormancy. Group B3 Raf protein kinases (B3-Rafs) serve as positive regulators of ABA and osmostress signaling in the moss Physcomitrium patens and the angiosperm Arabidopsis thaliana. While P. patens has a single B3-Raf called ARK, specific members of B3-Rafs among six paralogs regulate ABA and osmostress signaling in A. thaliana, indicating functional diversification of B3-Rafs in angiosperms. However, we found that the liverwort Marchantia polymorpha, belonging to another class of bryophytes, has three paralogs of B3-Rafs, MpARK1, MpARK2 and MpARK3, with structural variations in the regulatory domains of the polypeptides. By reporter assays of the P. patens ark line and analysis of genome-editing lines of M. polymorpha, we found that these B3-Rafs are functionally redundant in ABA response, with respect to inhibition of growth, tolerance to desiccation and expression of stress-associated transcripts, the majority of which are under the control of the PYR/PYL/RCAR-like receptor MpPYL1. Interestingly, gemmae in gemma cups were germinating only in mutant lines associated with MpARK1, indicating that dormancy in the gametophyte is controlled by a specific B3-Raf paralog. These results indicated not only conservation of the role of B3-Rafs in ABA and osmostress response in liverworts but also functional diversification of B3-Rafs, which is likely to have occurred in the early stages of land plant evolution.